Commutative encryption and authentication for OpenEXR high dynamic range images - Chen, Tzung-Her; Yan, Jing-Ya (Multimedia tools and applications, 2021)
For the sake of image security, confidentiality and integrity are always the first two concerns and can be further guaranteed by image encryption and authentication techniques, respectively. However, traditional image encryption and authentication for low dynamic range (LDR) images are not suitable to protect high dynamic range (HDR) images directly. Thus, encryption and authentication of HDR images should be redesigned and tailor-made. In this paper, a commutative HDR image encryption and authentication scheme is proposed to protect the promising one of HDR image formats, i.e., OpenEXR. Each HDR pixel value, which is recorded by 16-bit half floating-point numbers in the chunks part of the OpenEXR file layout, is split into the confidentiality part and the integrity part of the images. The most significant part is encrypted for confidentiality and the least significant one is used to embed the authentication bits. The proposed scheme not only guarantees the confidentiality and integrity of HDR images but also achieves format-compliance. To the best of our knowledge, this is the first attempt of research in terms of commutative encryption and authentication to HDR images. It enables the convenience or flexibility of verifying the integrity before/after decryption such that the proposed scheme is practical in real applications. The experimental results and theoretical analyses demonstrate that the proposed scheme does work well.